Overlexicality on Translation of Sexism Expression in The Novel The 19th Wife - Diajeng Sari; Sajarwa (Universitas Islam Negeri Palopo, 2025)
Overlexicality is lexical form to describe the lexical meaning in the translations works. The purpose of overlexicality is to create something to be eye catching and powerful but the translator still maintains the equivalence meaning from the source language to the target language. This research aims to focus on the how overlexicality occur in the sexism expression in a source text are translated into a target text. The study used qualitative descriptive method, the data in the forms of words, phrases, or sentences denoting sexism expression have been taken from the English novel The 19th Wife and its Indonesian translation, Istri ke-19. Based on the sampling data that has been analyze, the results show that the sexism expression related to hostile and benevolent were translated into overlexicalized. The translator used this method to emphasize the issues presented, however the results convey the sense that the translation depicts women in a very inferior and bad light because overlexicality occurs in sexist expressions related to sexual violence experienced by women.